Numerical Simulation in Transient Flow of Non-Newtonian Fluid in Nozzles - Sadikin, Azmahani; Mohd Bahrin, Mohd Khairul Anam; Ismail, Azzura; Ismail, Al Emran; Ahmad, Sufizar; Md Salleh, Salihatun; Abdol Rahman, Mohd Nasrull; Sapit, Azwan; Ayop, Sallehuddin Shah (International Journal of Integrated Engineering, 2018)
The rheological complexities of non-Newtonian fluids can lead to a variety of difficulties including most importantly changes in viscosity during packaging process. In order to give more understanding in this phenomena, the effect of temperature to the viscosity of chili sauce during packaging is investigated. This paper also presents the influence of three different shape of nozzles to the chili sauce flow behavior during filling time. A transient simulation has been conduct in this work using computational fluid dynamics (CFD) ANSYS CFX 15.0. It was found that viscosity is inversely proportional with temperature drop and time. The filling time also improved when using bigger conical angle of the nozzle. The results indicate the increased in production of the chilli sauce and improve packaging process.